Relationship Between Allergy and Chronic Rhinosinusitis - Munzir, Munzir; Delfitri, Munir; Andrina, Rambe Yunita Murni (Jurnal Biologi Tropis, 2025)
The role of allergy in chronic rhinosinusitis is still controversial. Numerous studies have demonstrated that atopy is highly prevalent in people with chronic rhinosinusitis (CRS), and that allergies may play a part in the pathogenesis of the condition. Allergy disorders, particularly those involving IgE-mediated in/flammation, are generally considered as triggering factors in the development of chronic rhinosinusitis or comorbidities/associated factors for the spread of chronic rhinosinusitis. The study aimed to determine the relationship between allergies and chronic rhinosinusitis. Observational analytical study with cross-sectional approach. 30 patients with symptoms of runny/blocked nose were examined. Allergy test, namely skin prick test, has been examined to categorize allergic and non-allergic patients. Total serum IgE and total eosinophil examination from blood were then categorized as increased and normal. The criteria for chronic rhinosinusitis are complaints of runny/blocked nose and facial pain and/or decreased sense of smell. Thirty patients (19 females and 11 males) aged 17 to 77 years were examined in this study. 19 patients were confirmed to have rhinosinusitis and 11 had rhinitis. The results of the analysis using the Chi Square test showed that there was no significant relationship between allergy, IgE, eosinophils, and chronic rhinosinusitis (p>0.05). There was no significant relationship between allergy, IgE, eosinophils with chronic rhinosinusitis.